Condylar Changes after Maxillary Expansion in Children with Cleft Lip and Palate—A Three-Dimensional Retrospective Study - Inês Carolina Graça; Inês Francisco; Adriana Guimarães; Francisco Caramelo; Francisco Vale (Biomimetics, 2022)
Background: The presence of posterior crossbite can trigger aesthetic and functional changes as mandibular asymmetry in individuals, contributing to asymmetrical muscle function. Mandibular asymmetry and respective condyle adaptation may be an etiological factor in temporomandibular disorder. This study aims to evaluate the effects of maxillary expansion on the position and angulation of the condyles as well as the intercondylar distance in children with cleft lip and palate. Methods: Twenty-five individuals with cleft lip and palate who underwent maxillary expansion were selected. Condylar changes were evaluated by cone beam computed tomography using the Pullinger and Hollender formula. To determine the statistically significant differences between the variables, the Student t-test and the Benjamini–Hochberg correction method for multiple comparisons were used. Results: No statistically significant differences between angulation and condylar position before and after maxillary expansion were found. The intercondylar distance tended to increase in growing individuals with cleft lip and palate after maxillary expansion. Conclusions: Intercondylar distance shows a tendency to increase after expansion regardless of the cleft phenotype. No differences were found in angulation and condylar position with the changes in occlusion resulting from maxillary expansion.